MEDIA PEMBELAJARAN MOTOR INDUKSI 1 PHASA PADA MATA KULIAH PRAKTIKUM MESIN LISTRIK DI PROGRAM STUDI S1 PENDIDIKAN TEKNIK ELEKTRO - Gede Gede Mahardika; I Gede Ratnaya; Wayan Mahardika Prasetya Wiratama (Jurnal Pendidikan Teknik Elektro Undiksha, 2021)
This study aims to create learning media for 1 Phase Induction Motors (Influence of Windings, Capacitors, and Voltage Variables) to determine the feasibility of the media, and to determine the student's responses to the media in the Electrical Machinery Practicum course in the Electrical Engineering Education Study Program Undiksha statistical data on the percentage of feasibility to process data from the content expert test and the media expert test, while for the small group test and large group test using the Five Scale Standard model data analysis. This study used a questionnaire as a data collection instrument. by content experts (materials), media experts, and students, from the results obtained from the content expert test, 81% of the qualifications were very feasible and the media expert test got a score of 95% on very decent qualifications, the small group test results on 4 students with very high qualifications, and the results of the large group trial of 13 students as respondents got results with very high qualifications. Based on the results of the research, the learning media of a 1-Phase Induction Motor (The Effect of Windings, Capacitors, and Voltage Variables) can be made suitable for use in the learning process in the Electrical Machinery Practicum course in the Electrical Engineering Education Study Program UNDIKSHA.